Models for the study of the local effects produced by a high-level radioactive waste repository - Ferreri, Juan Carlos; Grandi, Gerardo Marcelo (Comisión Nacional de Energía Atómica; Argentina, 1985)
Fil: Ferreri, Juan Carlos Comisión Nacional de Energía Atómica; Argentina